Nanosecond pulsed humid Ar plasma jet in air: shielding, discharge characteristics and atomic hydrogen production. (21st September 2017) - Yatom, Shurik; Luo, Yuchen; Xiong, Qing; Bruggeman, Peter J
Abstract: Gas phase non-equilibrium plasmas jets containing water vapor are of growing interest for many applications. In this manuscript, we report a detailed study of an atmospheric pressure nanosecond pulsed Ar  +  0.26% H2 O plasma jet. The plasma jet operates in an atmospheric pressure air surrounding but is shielded with a coaxial argon flow to limit the air diffusion into the jet effluent core. The jet impinges on a metal plate electrode and produces a stable plasma filament (transient spark) between the needle electrode in the jet and the metal plate. The stable plasma filament is characterized by spatially and time resolved electrical and optical diagnostics. This includes Rayleigh scattering, Stark broadening of the hydrogen Balmer lines and two-photon absorption laser induced fluorescence (TaLIF) to obtain the gas temperature, the electron density and the atomic hydrogen density respectively. Electron densities and atomic hydrogen densities up to 5 × 10 22 m − 3 and 2 × 10 22 m − 3 have been measured. This shows that atomic hydrogen is one of the main species in high density Ar-H2 O plasmas. The gas temperature does not exceed 550 K in the core of the plasma. To enable in situ calibration of the H TaLIF at atmospheric pressure a previously published O density calibration scheme is extended to include a correction for the line profiles by including overlap integrals as required by H TaLIF. The line width of H TaLIF, due to collision broadening has the same trend as the neutral density obtained by Rayleigh scattering. This suggests the possibility to use this technique to in situ probe neutral gas densities.